An Inverse Problem for Moore-Gibson-Thompson Equation Arising in High Intensity Ultrasound - Zamorano-Aliaga, S (De Gruyter Open Ltd, 2022)
In this article, we study the inverse problem of recovering a space-dependent coefficient of the Moore-Gibson-Thompson (MGT) equation from knowledge of the trace of the solution on some open subset of the boundary. We obtain the Lipschitz stability for this inverse problem, and we design a convergent algorithm for the reconstruction of the unknown coefficient. The techniques used are based on Carleman inequalities for wave equations and properties of the MGT equation. © 2022 Walter de Gruyter GmbH, Berlin/Boston.